Dynamic Roles of RNA and RNA Epigenetics in HTLV-1 Biology - Emily M. King; Amanda R. Panfil (Viruses)
Since the discovery of RNA in the early 1900s, scientific understanding of RNA form and function has evolved beyond protein coding. Viruses, particularly retroviruses like human T-cell leukemia virus type 1 (HTLV-1), rely heavily on RNA and RNA post-transcriptional modifications to regulate the viral lifecycle, pathogenesis, and evasion of host immune responses. With the emergence of new sequencing technologies in the last decade, our ability to dissect the intricacies of RNA has flourished. The ability to study RNA epigenetic modifications and splice variants has become more feasible with the recent development of third-generation sequencing technologies, such as Oxford nanopore sequencing. This review will highlight the dynamic roles of known RNA and post-transcriptional RNA epigenetic modifications within HTLV-1 biology, including viral hbz, long noncoding RNAs, microRNAs (miRNAs), transfer RNAs (tRNAs), R-loops, N6-methyladenosine (m6A) modifications, and RNA-based therapeutics and vaccines.